The Effect of the Project-Based Learning Model with a STEAM Approach on Students' Learning Interest and Mathematics Learning Outcomes in Grade VII - Grace Aprilin Latersia Br Trg; Mangaratua Marianus Simanjorang (Jurnal Pendidikan Matematika (JPM), 2025)
This study aims to determine the effect of the Project-Based Learning (PjBL) model with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on students’ learning interest and mathematics learning outcomes in Grade VII at SMP Negeri 1 Pancur Batu. This research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sampling technique used was cluster sampling, with two classes selected as samples: Class VII-2 as the experimental class, which received treatment using the PjBL model with the STEAM approach, and Class VII-1 as the control class, which was taught using a conventional learning model. The instruments used were a learning interest questionnaire and a mathematics learning outcomes test. The data analysis using an independent sample t-test showed a significant difference between students’ learning interest and learning outcomes in the experimental and control classes. The t-test significance value for learning interest was 0.013 < 0.05, and for learning outcomes was 0.001 < 0.05. Thus, it can be concluded that the Project-BasedProject-Based Learning model with the STEAM approach has a significant effect on improving learning interest and mathematics learning outcomes of Grade VII students.